Decisions Before Incisions: Technique Selection for the Distal Wedge Procedure. Issue 2 (12th March 2020) - Johnson, Thomas M.; Herold, Robert W.; Akers, Joshua A.; DiPirro, Daniel A.; Berridge, Joshua P.; McGary, Ryan T.
Abstract : Focused Clinical Question: What factors identify the optimal surgical technique when a distal wedge procedure is indicated at a terminal maxillary or mandibular molar site? Summary: Incision design for the distal wedge procedure is based primarily on the dental arch (maxilla or mandible), the distance from the terminal molar to the hamular notch or ascending ramus, and the dimensions of the attached gingiva. Conclusions: In most situations, favorable clinical results are achievable irrespective of the chosen distal wedge method, and technique selection is based more on operator preference than evidence. However, anatomic limitations can render distal wedge procedures challenging in some cases, and procedural advantages of specific techniques can simplify treatment. One systematic approach to distal wedge technique selection is presented in this report. Additionally, a laser‐assisted distal wedge protocol is presented for cases in which unfavorable tooth‐to‐ramus distance or presence of a prominent external oblique ridge contraindicates conventional distal wedge techniques.